(untitled) (Quinto Sol, 2026)
The development of Digital Humanities in Latin America has been hampered by deficiencies in infrastructure and digital literacy in the region, exacerbated by the lack of multidisciplinary approaches in universities and institutions. The Programming Historian is a project that originated in Canada in 2007 and has become a global infrastructure for the creation, research, and dissemination of content related to the autonomous development of computational skills by and for humanists. This article explores the challenges and strategies that enabled the construction of a global network of historians and humanists around a publication of methodological flows that address data-driven research. The Programming Historian not only contains tutorials but has also created a network of practice spanning multiple countries. It is argued that it has constituted a model of infrastructure, methodological literacy, and collaboration for leveraging common resources to create humanistic knowledge. Furthermore, it is noted that its model can be replicated in Latin America and other regions of the Global South to address the difficulties in building high-level infrastructure for the humanities.